Pendampingan Belajar Membaca Al-Qur’an Bagi Warga Desa Munggur Kecamatan Andong Boyolali - Indah Nurhidayati; Edy Muslimin; Malik Fajar; Safa Salwa Salsabila (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This community service program aims to enhance the knowledge and skills of reading the Qur'an among the residents of Munggur Village, Andong District, Boyolali Regency, through a structured learning assistance program. The primary target of this initiative is the village community, particularly children and teenagers, with sessions conducted from Monday to Saturday after Asr prayer at the Munggur Village Mosque. The results of this program indicate that the Qur'an Reading Assistance Program for the Residents of Munggur Village, Andong District, Boyolali Regency, 2025 was successfully implemented. The program's success was supported by active participation from parents, community members, village officials, and local government authorities. Additionally, the involvement of university students in directing the implementation methods significantly contributed to the smooth execution of the activities. However, some challenges were encountered, particularly the low interest of young children in learning to read the Qur'an using the tartil method. Therefore, more innovative strategies are needed to increase their motivation for learning in the future.